Methodology Proposal for Appraising Health Service Ict System Implication - Watkins-Orellana, F; Oddershede-Herrera, A; Quezada-Llanca, L (Institute of Electrical and Electronics Engineers Inc., 2018)
A decision making methodology is proposed as support and guidance to evaluate an Information and Communications Technology system (ICT) in healthcare service processes involving agents perspective. Through multicriteria approach, by the use of the Analytic Hierarchy Process (AHP), pilot studies are carried out in health institutions in Chile to examine ICT system demands, ICT infrastructure available, and the relative importance of quality of service needs. The results will give information to assist decision makers for resource distribution. The proposed conceptual prototype offer a base for detecting the more relevant ICT system to perform health service and to dimension the crucial factors concerning quality of service issues. © 2018 IEEE.